APLIKASI REKAM MEDIS BERBASIS SMS GATEWAY - Gusti Made Cahya Wiarjaya; Bambang Pramono; Rahmat Ramadhan (Informatics Engineering Department of Halu Oleo University, 2016)
The development of information technology has developed very rapidly following the age requirements that require speed and accuracy in all aspects of life. Follow developments in terms of hardware, software, and in terms of human resources to operate them. At this time almost all areas of life need information technology and human behavior are used to applying information technology in everyday life. With computers we can perform data processing and data storage. Can then input data, edit data, save, delete, etc., so the data is managed more effectively and efficiently. With rapid advances in technology today, bring an idea or ideas of the writer to try to computerize records Medical Records. The author tries to build an application that will help to simplify the processing of medical data include patient data, physician data, and drug data, with the aim to make easy in data processing more optimal and effective. The system that will be made is ”Application Information System Based Medical Record SMS Gateway”. This application was made using modeling Unified Modeling Language (UML), gammu tools to build their SMS gateway application, Php as web programming language and MySQL as data storage. Keywords— SMS Gateway, Gammu, Php, MySQL.